Nonaqueous electrolyte secondary battery
By adding lithium-containing composite oxides and sulfonic acid compounds to the positive electrode active substance of the nonaqueous electrolyte secondary battery and using sulfur-containing compounds in the nonaqueous electrolyte, the shortcomings of the battery in high capacity and charge and discharge cycle characteristics are solved, and efficient battery performance stability is achieved.
Patent Information
- Application Number
- CN202380060664.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-08-23
- Filing Date
- 2023-07-18
- Publication Date
- 2025-04-01
AI Technical Summary
The existing nonaqueous electrolyte secondary batteries have shortcomings in high capacity and improving charge and discharge cycle characteristics, especially the problem of resistance changes under high temperature conditions cannot be effectively suppressed.
A positive electrode active material is used, which contains a lithium-containing composite oxide and a sulfonic acid compound present on its surface, and a sulfur-containing compound is added to the non-aqueous electrolyte to form a good surface state that inhibits side reactions.
A nonaqueous electrolyte secondary battery that achieves high capacity and improves charge and discharge cycle characteristics can effectively suppress resistance changes under high temperature conditions and improve the performance stability of the battery.
Smart Images

Figure CN119744466A_ABST
Abstract
Description
Technical Field
[0001] The present disclosure relates to a nonaqueous electrolyte secondary battery. Background Art
[0002] In recent years, the use of nonaqueous electrolyte secondary batteries has expanded to power sources for electric vehicles, power storage devices for utilizing natural energy, etc. The properties required of positive electrode active materials used in nonaqueous electrolyte secondary batteries also vary depending on the use.
[0003] Patent document 1 proposes a lithium titanate powder for an electrode of an electric storage device, wherein the lithium titanate powder is Li4Ti5O 12 The particle has a surface layer as a main component on at least a part of the particle surface, and the surface layer contains a lithium sulfonate compound having an alkyl group having 1 to 5 carbon atoms or an aryl group having 6 to 12 carbon atoms.
[0004] Prior art literature
[0005] Patent Literature
[0006] Patent Document 1: Japanese Patent Application Publication No. 2018-6164 Summary of the invention
[0007] Problem that the invention aims to solve
[0008] Patent Document 1 aims to suppress the change in resistance of an electric storage device before and after long-term high-temperature charging and storage. However, there is still much room for improvement in increasing the capacity of nonaqueous electrolyte secondary batteries and improving charge-discharge cycle characteristics.
[0009] Solutions for solving problems
[0010] One aspect of the present invention relates to a non-aqueous electrolyte secondary battery comprising a positive electrode, a negative electrode and a non-aqueous electrolyte, wherein the positive electrode comprises a positive electrode active material, the positive electrode active material comprises a lithium-containing composite oxide and a sulfonic acid compound present on the surface of the lithium-containing composite oxide, and the non-aqueous electrolyte comprises a sulfur-containing compound.
[0011] Effects of the Invention
[0012] According to the present disclosure, it is possible to provide a nonaqueous electrolyte secondary battery that is advantageous in increasing capacity and improving charge and discharge cycle characteristics.
[0013] The novel features of the present invention are described in the appended claims, but both the composition and content of the present invention should be more fully understood from the following detailed description with reference to the accompanying drawings, together with other objects and features of the present invention. BRIEF DESCRIPTION OF THE DRAWINGS
[0014] Figure 1It is a longitudinal cross-sectional view of a nonaqueous electrolyte secondary battery according to one embodiment of the present disclosure. DETAILED DESCRIPTION
[0015] Hereinafter, the embodiments of the present disclosure will be described using examples, but the present disclosure is not limited to the examples described below. In the following description, specific numerical values and materials are sometimes listed, but other numerical values and materials may also be used as long as the effects of the present disclosure can be obtained. In this specification, the expression "numerical value A to numerical value B" includes numerical value A and numerical value B, and can be understood as "above numerical value A and below numerical value B". In the following description, when the lower limit and upper limit of numerical values related to specific physical properties or conditions are shown, as long as the lower limit is not above the upper limit, any exemplified lower limit and any exemplified upper limit can be arbitrarily combined. When multiple materials are exemplified, one of them can be selected and used alone, or two or more can be used in combination.
[0016] In addition, the present disclosure includes a combination of matters described in two or more claims arbitrarily selected from the plurality of claims recorded in the attached claims. That is, as long as no technical contradiction occurs, matters described in two or more claims arbitrarily selected from the plurality of claims recorded in the attached claims may be combined.
[0017] In the following description, the term "comprising" or "including" includes expressions such as "containing (or including)", "consisting essentially of", and "consisting of".
[0018] Secondary batteries include at least non-aqueous electrolyte secondary batteries such as lithium ion batteries and lithium metal secondary batteries.
[0019] The nonaqueous electrolyte secondary battery according to the present embodiment includes a positive electrode, a negative electrode, and a nonaqueous electrolyte. The positive electrode includes a positive electrode active material, and the positive electrode active material includes a lithium-containing composite oxide and a sulfonic acid compound present on the surface of the lithium-containing composite oxide.
[0020] Here, the surface of the lithium-containing composite oxide may be the surface of the secondary particles of the lithium-containing composite oxide, the surface of the primary particles, or the interface where the primary particles are in contact with each other. The lithium-containing composite oxide generally includes secondary particles formed by the aggregation of primary particles. That is, the sulfonic acid compound is present on at least one of the surface of the secondary particles of the lithium-containing composite oxide, the surface of the primary particles, or the interface where the primary particles are in contact with each other.
[0021] At least a portion of the sulfonic acid compound is insoluble in the non-aqueous electrolyte and maintains a solid state on the surface of the lithium-containing composite oxide. The sulfonic acid compound has a barrier effect of protecting the surface of the lithium-containing composite oxide and inhibiting the side reaction of the lithium-containing composite oxide and the non-aqueous electrolyte. The sulfonic acid compound can also inhibit the increase of the reaction resistance at the surface of the lithium-containing composite oxide.
[0022] Next, the non-aqueous electrolyte contains a sulfur-containing compound. At least a portion (usually all) of the sulfur-containing compound in the non-aqueous electrolyte is dissolved in the non-aqueous electrolyte, so it can always act on the surface of the lithium-containing composite oxide. It can be considered that not only the sulfonic acid compound is present on the surface of the lithium-containing composite oxide, but also the non-aqueous electrolyte contains a sulfur-containing compound, thereby forming a good surface state on the lithium-containing composite oxide that suppresses side reactions. For example, the sulfur-containing compound acts between the surface of the lithium-containing composite oxide and the sulfonic acid compound, or may also act on an area not covered by the dispersed particulate sulfonic acid compound. In this case, the surface state of the lithium-containing composite oxide is similar to the state of a dense and low-resistance protective coating.
[0023] Even if the nonaqueous electrolyte contains a sulfur-containing compound, if the sulfonic acid compound is not present on the surface of the lithium-containing composite oxide, it is difficult to obtain the effect of suppressing the side reaction. This is probably because the sulfur-containing compound does not fully act on the surface of the lithium-containing composite oxide.
[0024] On the other hand, when the non-aqueous electrolyte contains a sulfur-containing compound and the sulfonic acid compound is present on the surface of the lithium-containing composite oxide, the sulfur-containing compound can effectively act on the surface of the lithium-containing composite oxide. As a result, side reactions are significantly suppressed compared to when only the sulfonic acid compound is used. In other words, the sulfur-containing compound in the non-aqueous electrolyte has the effect of enhancing the protective effect of the sulfonic acid compound on the lithium-containing composite oxide.
[0025] The sulfonic acid compound only needs to contact the surface of the particles of the lithium-containing composite oxide. The sulfonic acid compound can cover at least a portion of the surface of the particles of the lithium-containing composite oxide. The sulfonic acid compound can be attached to or precipitated on the surface of the particles of the lithium-containing composite oxide. The sulfonic acid compound can form particles smaller than the particles of the lithium-containing composite oxide, and can form an island film covering at least a portion of the surface of the particles of the lithium-containing composite oxide.
[0026] Hereinafter, each constituent element of the nonaqueous electrolyte secondary battery according to the present disclosure will be described in more detail.
[0027] [positive electrode]
[0028] The positive electrode comprises a positive electrode collector and a positive electrode mixture layer arranged on the surface of the positive electrode collector. The positive electrode collector is composed of a sheet-shaped conductive material. The positive electrode mixture layer is carried on one side or both sides of the positive electrode collector. The positive electrode mixture layer is usually a layer or film composed of a positive electrode mixture. The thickness of the positive electrode mixture layer is, for example, 10 μm to 150 μm per side of the positive electrode collector. The positive electrode mixture contains a positive electrode active material as an essential component. The positive electrode active material contains a lithium-containing composite oxide and a sulfonic acid compound present on the surface of the lithium-containing composite oxide.
[0029] The positive electrode mixture layer may contain a conductive agent as an arbitrary component. As the conductive agent, for example, carbon black (CB), acetylene black (AB), Ketjen black, carbon nanotubes (CNT), graphene, graphite and other carbon-based materials can be listed. They can be used alone or in combination of two or more.
[0030] The positive electrode mixture layer may include a binder. As the binder, for example, fluorine resins such as polytetrafluoroethylene (PTFE), polyvinylidene fluoride (PVDF), polyacrylonitrile (PAN), polyimide resins, acrylic resins, polyolefin resins, etc. may be listed. They may be used alone or in combination of two or more.
[0031] As the positive electrode current collector, a nonporous conductive substrate (metal foil, etc.) or a porous conductive substrate (grid, net, punched sheet, etc.) is used. Examples of the material of the positive electrode current collector include aluminum, aluminum alloy, titanium, titanium alloy, and the like.
[0032] (Sulfonic acid compound)
[0033] The sulfonic acid compound is an organic compound having a sulfonic acid group (SO3H) or an organic compound having a salt of a sulfonic acid group. The sulfonic acid compound may be a monosulfonic acid compound having only one sulfonic acid group (SO3H), a disulfonic acid compound having two sulfonic acid groups (SO3H), or a polysulfonic acid compound having three or more sulfonic acid groups (SO3H). The valence of the cation of the salt of the sulfonic acid group may be monovalent or divalent or more. The sulfonic acid compound may be used alone or in combination of two or more.
[0034] The sulfonic acid compound is represented by, for example, the general formula (I).
[0035]
[0036] In the general formula (I), A is a Group 1 element or a Group 2 element. A is preferably a Group 1 element, more preferably Li. As a result, the surface state of the lithium-containing composite oxide becomes a state with lower resistance, and the output characteristics can also be improved. It should be noted that when A is a Group 1 element, n=1.
[0037] In the general formula (I), R is a hydrocarbon group, preferably an alkyl group. R may be an alkyl group having 5 or less carbon atoms, or an alkyl group having 3 or less carbon atoms, but is preferably a methyl group. In addition, a portion of the carbon-bonded hydrogen in R may be substituted with fluorine. However, not all of the carbon-bonded hydrogen in R may be substituted with fluorine. The smaller the molecular weight of R, the more the reaction resistance can be reduced.
[0038] Specific examples of the sulfonic acid compound include lithium methanesulfonate, lithium ethanesulfonate, lithium propanesulfonate, sodium methanesulfonate, magnesium methanesulfonate, and lithium fluoromethanesulfonate.
[0039] The amount of the sulfonic acid compound present on the surface of the lithium-containing composite oxide may be, for example, 0.1 mass % to 1 mass % or 0.3 mass % to 0.8 mass % relative to the mass of the lithium-containing composite oxide.
[0040] The presence of the sulfonic acid compound on the surface of the lithium-containing composite oxide can be confirmed by Fourier transform infrared spectroscopy (FT-IR). In the infrared absorption spectrum obtained by FT-IR, the positive electrode active material can be detected at 1238 cm -1 、1175cm -1 、1065cm -1 、785cm -1 At least one or more locations nearby have an absorption peak.
[0041] In the infrared absorption spectrum obtained by FT-IR, for example, the positive electrode active material containing lithium methanesulfonate has an absorption spectrum at 1238 cm -1 、1175cm -1 、1065cm -1 、785cm -1 There is an absorption peak near 1238cm -1 、1175cm -1 、1065cm -1 The nearby peak is due to the SO stretching vibration of lithium methanesulfonate. 785cm -1 The nearby peak is an absorption peak due to CS stretching vibration derived from lithium methanesulfonate.
[0042] Even in the positive electrode active material containing a sulfonic acid compound other than lithium methanesulfonate, the absorption peak from the sulfonic acid compound contained in the positive electrode active material can be identified, as in the positive electrode active material containing lithium methanesulfonate. It should be noted that the presence of the sulfonic acid compound at the surface of the lithium-containing composite oxide can also be confirmed by ICP, atomic absorption spectroscopy, X-ray photoelectron spectroscopy (XPS), radiation light XRD measurement, TOF-SIMS, etc.
[0043] The average particle size of the granular sulfonic acid compound is, for example, 100 μm or less, 50 μm or less, 30 μm or less, or 15 μm or less. In this case, the sulfonic acid compound can be more uniformly attached to the entire positive electrode active material powder, and the effect of the sulfonic acid compound can be more significantly manifested. The lower limit of the average particle size of the sulfonic acid compound is, for example, 1 μm.
[0044] Here, the average particle size of the sulfonic acid compound can be determined by observing the sulfonic acid compound on the surface of the lithium-containing composite oxide using SEM. Specifically, the outer shapes of 50 randomly selected particles are determined, the major diameter (longest diameter) of each of the 50 particles is determined, and their average value is taken as the average particle size of the sulfonic acid compound.
[0045] (Lithium-containing composite oxide)
[0046] The particle size of the primary particles constituting the secondary particles of the lithium-containing composite oxide is, for example, 0.02 μm to 20 μm. The particle size of the primary particles is measured as the diameter of the circumscribed circle in the particle image observed by a scanning electron microscope (SEM). The average particle size of the secondary particles of the lithium-containing composite oxide is, for example, 20 μm to 300 μm. Here, the average particle size refers to the median particle size (D50) based on volume. D50 refers to the particle size when the cumulative volume from the small particle size side in the volume-based particle size distribution reaches 50%. The particle size distribution of the secondary particles of the lithium-containing composite oxide can be measured using a laser diffraction particle size distribution measuring device (e.g., MT3000II manufactured by Microtrac Bell) and water as the dispersion medium.
[0047] The lithium-containing composite oxide may have a layered rock salt structure. The layered rock salt structure, for example, belongs to the space group R-3m, the space group C2 / m, etc. Among them, the layered rock salt structure belonging to the space group R-3m is preferred because of its high capacity and high stability of the crystal structure. The layered rock salt structure of the lithium-containing composite oxide may include a transition metal layer, a Li layer, and an oxygen layer.
[0048] From the viewpoint of increasing capacity, the ratio of Ni in the metal elements other than Li contained in the lithium-containing composite oxide (Ni content) may be 50 atomic % or more, 80 atomic % or more, or 90 atomic % or more.
[0049] From the perspective of stabilizing the crystal structure of the lithium-containing composite oxide and improving the heat resistance of the battery, the ratio of Co in the metal elements other than Li contained in the lithium-containing composite oxide (Co content) can be set to 0 atomic % or more, or to 1.5 atomic % or more. In addition, the Co content can be set to 20 atomic % or less, 16 atomic % or less, or 10 atomic % or less.
[0050] Similarly, from the perspective of stabilizing the crystal structure of the lithium-containing composite oxide and improving the heat resistance of the battery, the ratio of Al in the metal elements other than Li contained in the lithium-containing composite oxide (Al content) can be set to 0 atomic % or more, 3.5 atomic % or more, or 4 atomic % or more. In addition, the Al content can be set to 18.5 atomic % or less, or 10 atomic % or less.
[0051] From the perspective of cost reduction, the proportion of Mn in the metal elements other than Li contained in the lithium-containing composite oxide (Mn content) can be set to 0 atomic % or more, or to 5 atomic % or more. In addition, the Mn content can be set to 50 atomic % or less, or to 30 atomic % or less.
[0052] The content of each metal element contained in the lithium-containing composite oxide is measured by, for example, inductively coupled plasma (ICP) emission spectrometry.
[0053] The lithium-containing composite oxide may be, for example, of the general formula Li a Ni x Co y Al z M1 w O 2-b The composite oxide shown in the formula, wherein 0.8≤a≤1.2, 0.615≤x≤0.95, 0.015≤y≤0.20, 0.035≤z≤0.185, 0≤w≤0.145, 0≤b<0.05, x+y+z+w=1, and M1 is at least one element selected from Mn, Fe, Ti, Si, Nb, Zr, Mo and Zn. In this case, M1 is preferably Mn.
[0054] Next, an example of a method for producing a positive electrode active material according to the present embodiment is described. The method for producing a positive electrode active material includes, for example, a synthesis step, a washing step, a drying step, and an adding step.
[0055] In the synthesis step, a transition metal oxide and a Li compound are mixed and calcined to obtain a lithium-containing composite oxide.
[0056] The transition metal oxide can be obtained, for example, by stirring a solution of a metal salt containing a metal element such as Ni, Co, Al, or Mn, while dropping an alkaline solution such as sodium hydroxide to adjust the pH to the alkaline side (e.g., 8.5 to 12.5), precipitating a composite hydroxide (coprecipitation), and heat-treating the composite hydroxide. The heat treatment temperature is not particularly limited, and is, for example, in the range of 300° C. to 600° C.
[0057] As the Li compound, for example, Li2CO3, LiOH, Li2O2, Li2O, LiNO3, LiNO2, Li2SO4, LiOH·H2O, LiH, LiF, etc. can be cited. The mixing ratio of the metal oxide and the Li compound is preferably set to a ratio in the range of 1:0.98 to 1:1.1 in the molar ratio of the metal element other than Li:Li. It should be noted that when the transition metal oxide and the Li compound are mixed, other metal raw materials can be added as needed. Here, other metal raw materials are oxides of metal elements other than the metal elements constituting the transition metal oxide, etc.
[0058] The mixture of transition metal oxide and Li compound is calcined, for example, in an oxygen atmosphere. Regarding the calcination conditions, the heating rate at 450°C or above and 680°C or below is greater than 1.0°C / minute and is in the range of 5.5°C / minute or below, and the maximum temperature reached can be in the range of 700°C or above and 850°C or below. The heating rate from greater than 680°C to the maximum temperature can be, for example, 0.1°C / minute to 3.5°C / minute. In addition, the holding time to the maximum temperature can be greater than 1 hour and less than 10 hours. In addition, the calcination process can be a multi-stage calcination, and the first heating rate and the second heating rate can be set multiple in each temperature zone, as long as they are within the above-mentioned specified range.
[0059] In the washing step, the lithium-containing composite oxide obtained in the synthesis step is washed with water and dehydrated to obtain a filter cake-like composition. The washing and dehydration can be performed using known methods and conditions. It can be performed within a range where lithium does not dissolve from the lithium-containing composite oxide and cause degradation of battery characteristics. It should be noted that the positive electrode active material involved in this embodiment has less residual alkali components because it is washed with water.
[0060] In the drying step, the cake-like composition obtained in the washing step is dried. The drying step can be performed in a vacuum atmosphere. The drying conditions are, for example, 150° C. to 400° C. and 0.5 to 15 hours.
[0061] In the adding process, at least one of a sulfonic acid compound and a solution of sulfonic acid (e.g., an aqueous solution) is added to the filter cake-like composition obtained in the washing process or the composition obtained in the drying process. Thus, the sulfonic acid compound can be attached to the surface of the lithium-containing composite oxide. Preferably, at least one of a sulfonic acid compound and a solution of sulfonic acid is added to the filter cake-like composition. Since a Li compound remains in the filter cake-like composition and the residual Li compound is dissolved in the water contained in the filter cake-like composition, a sulfonic acid compound containing Li is formed even when a solution of sulfonic acid is added. The amount of the sulfonic acid compound added is preferably 0.1% to 1% by mass, and more preferably 0.3% to 0.8% by mass, relative to the mass of the lithium-containing composite oxide. The concentration of the sulfonic acid solution is, for example, 0.5% to 40% by mass.
[0062] For example, a raw material containing a metal compound containing one or more metal elements selected from the group consisting of Sr, Ca, W, Zr, rare earths and Al and a non-metal compound containing one or more non-metal elements selected from the group consisting of P and B can be added during the synthesis process, after the synthesis process, during the cleaning process, after the cleaning process, during the drying process, after the drying process, or during the adding process. In this way, a metal compound containing one or more metal elements selected from the group consisting of Sr, Ca, W, Zr, rare earths and Al and a non-metal compound containing one or more non-metal elements selected from the group consisting of P and B can be attached to the surface of the lithium-containing composite oxide.
[0063] Examples of Sr raw materials include Sr(OH)2, Sr(OH)2·8H2O, SrO, SrCo3, SrSO4, Sr(NO3)2, SrCl2, SrAlO4, etc. Examples of Ca raw materials include Ca(OH)2, CaO, CaCO3, CaSO4, Ca(NO3)2, CaCl2, CaAlO4, etc. Examples of Zr raw materials include Zr(OH)4, ZrO2, Zr(CO3)2, Zr(SO4)2·4H2O, etc. Examples of rare earth raw materials include oxides, hydroxides, carbonates, etc. Examples of W raw materials include tungsten oxide (WO3), lithium tungstate (Li2WO4, Li4WO5, Li6W2O9), etc. It should be noted that as a W raw material, a solution containing W can be used. In addition, Al2O3, Al(OH)3, Al2(SO4)3, etc. can be used as Al raw materials, but Al from lithium-containing composite oxides can also be used. As P raw materials, Li 3-x H x PO4 (0≤x≤3), etc. Examples of B raw materials include H3BO3, Li3BO3, and Li2B4O7.
[0064] [negative electrode]
[0065] The negative electrode at least has a negative electrode collector, and may have a negative electrode mixture layer arranged on the surface of the negative electrode collector. The negative electrode collector is composed of a sheet-like conductive material. The negative electrode mixture layer is carried on one or both sides of the negative electrode collector. The negative electrode mixture layer is usually a layer or film composed of a negative electrode mixture. The thickness of the negative electrode mixture layer is, for example, 10μm to 150μm per side of the negative electrode collector. The negative electrode mixture contains a negative electrode active material as an essential component, and may contain a binder, a conductive agent, a thickener, etc. as arbitrary components. As a binder, a conductive agent, and a thickener, known materials can be used.
[0066] The negative electrode active material includes materials that electrochemically absorb and release lithium ions, lithium metal, lithium alloys, etc. As materials that electrochemically absorb and release lithium ions, carbon materials, alloy materials, etc. can be used. As carbon materials, for example, graphite, easily graphitized carbon (soft carbon), and difficultly graphitized carbon (hard carbon) can be listed. Among them, graphite with excellent charge and discharge stability and low irreversible capacity is preferred. Alloy materials are materials containing at least one metal that can form an alloy with lithium. As such materials, silicon, tin, silicon alloys, tin alloys, silicon compounds, etc. can be listed. Silicon oxide, tin oxide, etc. can also be used.
[0067] As the alloy material containing silicon, for example, a silicon-containing material including a lithium ion conductive phase and a silicon phase dispersed in the lithium ion conductive phase can be preferably used.
[0068] As the lithium ion conductive phase, for example, a silicon oxide phase, a silicate phase, a carbon phase, etc. can be used. The main component (for example, 95 to 100% by mass) of the silicon oxide phase can be silicon dioxide. The silicate phase is preferred because it has a small irreversible capacity. Among them, as a lithium ion conductive phase with high initial charge and discharge efficiency, a silicate phase containing lithium (hereinafter also referred to as a lithium silicate phase) can be preferably used.
[0069] The lithium silicate phase can be any oxide phase containing lithium (Li), silicon (Si), and oxygen (O), and can also contain other elements. The atomic ratio of O to Si in the lithium silicate phase: O / Si is, for example, greater than 2 and less than 4. Preferably, O / Si is greater than 2 and less than 3. The atomic ratio of Li to Si in the lithium silicate phase: Li / Si is, for example, greater than 0 and less than 4. The lithium silicate phase can have the formula: Li 2z SiO 2+z The composition is shown as (0<z<2). z preferably satisfies the relationship of 0<z<1, and z=1 / 2 is more preferred. Elements other than Li, Si and O that may be contained in the lithium silicate phase include, for example, iron (Fe), chromium (Cr), nickel (Ni), manganese (Mn), copper (Cu), molybdenum (Mo), zinc (Zn), aluminum (Al) and the like.
[0070] The carbon phase may be composed of, for example, amorphous carbon (ie, non-crystalline carbon) having low crystallinity. The amorphous carbon may be, for example, hard carbon, soft carbon, or other carbon.
[0071] As the negative electrode active material, a silicon-containing material and a carbon material can be used in combination. Since the silicon-containing material expands and contracts in volume with charging and discharging, if the proportion of the silicon-containing material in the negative electrode active material increases, poor contact between the negative electrode active material and the negative electrode collector is likely to occur with charging and discharging. On the other hand, by using a silicon-containing material and a carbon material in combination, excellent cycle characteristics can be achieved while giving the negative electrode a high capacity.
[0072] The ratio of the silicon-containing material to the total of the silicon-containing material and the carbon material is, for example, preferably 0.5 to 15% by mass, more preferably 1 to 10% by mass. This makes it easier to achieve both high capacity and improved cycle characteristics.
[0073] As the negative electrode current collector, a nonporous conductive substrate (metal foil, etc.) or a porous conductive substrate (grid, net, punched sheet, etc.) is used. Examples of the material of the negative electrode current collector include stainless steel, nickel, nickel alloy, copper, copper alloy, and the like.
[0074] [Non-aqueous electrolyte]
[0075] The non-aqueous electrolyte includes a non-aqueous solvent and a solute dissolved in the non-aqueous solvent. The solute includes, for example, a lithium salt. Components other than the non-aqueous solvent and the solute of the non-aqueous electrolyte are additives. Various additives may be included in the non-aqueous electrolyte.
[0076] In the present disclosure, a sulfur-containing compound is used as an essential component in particular among the additives. The nonaqueous electrolyte may contain one sulfur-containing compound or a combination of two or more sulfur-containing compounds.
[0077] Since the non-aqueous electrolyte contains a sulfur-containing compound, a highly flexible solid electrolyte interface (Solid Electrolyte Interphase: SEI) is formed on the surface of the negative electrode active material. The highly flexible SEI easily follows the expansion and contraction of the negative electrode due to charge and discharge. Therefore, it can be considered that even if charge and discharge are repeated, the reduction in capacity can be reduced and high cycle characteristics can be obtained.
[0078] The sulfur-containing compound preferably has one or more sulfonyl groups (-S(=O)2-), and may have one or more fluorosulfonyl groups (FS(=O)2-). For example, the sulfur-containing compound may contain fluorosulfonic acid or fluorosulfonate. Among fluorosulfonates, lithium fluorosulfonate is preferred.
[0079] As the sulfur-containing compound, at least one selected from the group consisting of sulfate esters, sulfite esters, sulfonate esters, and sulfonimide compounds can be used.
[0080] Sulfate esters have a -OS(=O)2-O- structure. Sulfate esters may be cyclic or chain-shaped, or may form salts. 2-4 Alkyl sulfate esters: Specifically, ethylene sulfate, propylene sulfate, trimethylene sulfate, butylene sulfate, vinylene sulfate, ethyl sulfate, methyl sulfate, etc. are mentioned.
[0081] Sulfite has a -OS(=O)-O- structure. Sulfite may be cyclic or chain-shaped, or may form a salt. As sulfite, C 2-4 Alkylene sulfite. Specific examples thereof include ethylene sulfite (ES), propylene sulfite, trimethylene sulfite, butylene sulfite, and vinylene sulfite.
[0082] Sulfonic acid esters have a -S(=O)2-O- structure. Sulfonic acid esters may be cyclic or chain-shaped, or may form salts. As sulfonic acid esters, preferably selected from C 3-5 Alkanesultones and C 3-5 At least one of the group consisting of olefin sultones. Among them, cyclic sulfonates are preferred. Specifically, 1,3-propane sultone, 1,4-butane sultone, 1,3-propene sultone, etc. are listed.
[0083] As the sulfonyl imide compound, an imide salt can be used. As the imide salt, lithium bis(fluorosulfonyl imide) (LiN(FSO2)2), lithium bis(trifluoromethanesulfonyl imide) (LiN(CF3SO2)2), lithium trifluoromethanesulfonyl imide (LiN(CF3SO2)(C4F9SO2)), lithium bis(pentafluoroethanesulfonyl imide) (LiN(C2F5SO2)2), etc. can be listed. The non-aqueous electrolyte can contain one imide salt or a combination of two or more.
[0084] In the case of the sulfur-containing compound, one or more hydrogen atoms in the above-mentioned compounds may be substituted by a substituent. Examples of the substituent include an alkyl group, a hydroxyalkyl group, a hydroxyl group, an alkoxy group, and a halogen atom. The number of carbon atoms in the substituent may be 1 to 4 or 1 to 3. Examples of the halogen atom include a chlorine atom and a fluorine atom.
[0085] The content of the sulfur-containing compound contained in the non-aqueous electrolyte is, for example, 0.01% by mass or more and 10% by mass or less. The content of the sulfur-containing compound in the non-aqueous electrolyte may be 5% by mass or less, 3% by mass or less, or 2% by mass or less. The content of the sulfur-containing compound in the non-aqueous electrolyte may be 0.1% by mass or more, or 0.5% by mass or more. When the content of the sulfur-containing compound is within such a range, the viscosity of the non-aqueous electrolyte can be suppressed to be relatively low and the charge-discharge reaction can be carried out more uniformly.
[0086] It should be noted that the content of sulfur-containing compounds in the non-aqueous electrolyte of a non-aqueous electrolyte secondary battery changes during storage or during charge and discharge cycles. Therefore, the sulfur-containing compounds may remain in the non-aqueous electrolyte extracted from the non-aqueous electrolyte secondary battery at a concentration above the detection limit.
[0087] The non-aqueous electrolyte may contain other additives. Examples of such additives include vinyl ethylene carbonate and cyclohexylbenzene.
[0088] As the non-aqueous solvent, for example, cyclic carbonates, chain carbonates, cyclic carboxylates, chain carboxylates, etc. can be used. As cyclic carbonates, propylene carbonate (PC), ethylene carbonate (EC), vinylene carbonate (VC), etc. can be listed. As chain carbonates, diethyl carbonate (DEC), ethyl methyl carbonate (EMC), dimethyl carbonate (DMC), etc. can be listed. In addition, as cyclic carboxylates, γ-butyrolactone (GBL), γ-valerolactone (GVL), etc. can be listed. As chain carboxylates, methyl acetate, ethyl acetate, propyl acetate, methyl propionate (MP), ethyl propionate (EP), etc. can be listed. The non-aqueous solvent can be used alone or in combination of two or more.
[0089] As the lithium salt, for example, a lithium salt containing chloric acid (LiClO4, LiAlCl4, LiB 10 Cl 10 etc.), lithium salts of fluorinated acids (LiPF6, LiPF2O2, LiBF4, LiSbF6, LiAsF6, LiCF3SO3, LiCF3CO2, etc.), lithium salts of fluorinated imides (LiN(FSO2)2, LiN(CF3SO2)2, LiN(CF3SO2)(C4F9SO2), LiN(C2F5SO2)2, etc.), lithium halides (LiCl, LiBr, LiI, etc.), etc. The lithium salts may be used alone or in combination of two or more.
[0090] The concentration of the lithium salt in the non-aqueous electrolyte may be 1 mol / L or more and 2 mol / L or less, or 1 mol / L or more and 1.5 mol / L or less. By controlling the lithium salt concentration within the above range, an electrolyte having excellent ion conductivity and appropriate viscosity may be obtained. The lithium salt concentration is not limited to the above concentration.
[0091] [Separator]
[0092] Preferably, a separator is sandwiched between the positive electrode and the negative electrode. The separator has high ion permeability and has appropriate mechanical strength and insulation. As the separator, a microporous film, a woven fabric, a non-woven fabric, etc. can be used. As the material of the separator, polyolefins such as polypropylene and polyethylene are preferred.
[0093] <Non-aqueous electrolyte secondary battery>
[0094] As an example of the structure of a non-aqueous electrolyte secondary battery, an electrode group formed by winding a positive electrode and a negative electrode across a separator and being contained in an outer body together with a non-aqueous electrolyte can be cited. However, it is not limited to this, and other forms of electrode groups can also be applied. For example, a stacked electrode group formed by stacking a positive electrode and a negative electrode across a separator can also be used. The form of the secondary battery is also not limited to this, for example, a cylindrical type, a square type, a coin type, a button type, a laminated type, etc.
[0095] Below, refer to Figure 1 The structure of the nonaqueous electrolyte secondary battery will be described. Figure 1 1 is a longitudinal cross-sectional view of a cylindrical secondary battery 10 according to an example of the present embodiment. However, the present disclosure is not limited to the following configuration.
[0096] The secondary battery 10 includes an electrode group 18, an electrolyte (not shown), and a bottomed cylindrical battery can 22 for accommodating them. The sealing body 11 is tightly fitted and fixed to the opening of the battery can 22 via a sealing gasket 21. The interior of the battery is thus sealed. The sealing body 11 includes: a valve body 12, a metal plate 13, and an annular insulating member 14 sandwiched between the valve body 12 and the metal plate 13. The valve body 12 and the metal plate 13 are connected to each other at their respective center portions. The positive electrode lead 15a led out from the positive electrode 15 is connected to the metal plate 13. Therefore, the valve body 12 acts as an external terminal of the positive electrode. The negative electrode lead 16a led out from the negative electrode 16 is connected to the bottom inner surface of the battery can 22. An annular groove portion 22a is formed near the open end of the battery can 22. A first insulating plate 23 is arranged between one end surface of the electrode group 18 and the annular groove portion 22a. A second insulating plate 24 is disposed between the other end surface of the electrode group 18 and the bottom of the battery can 22. The electrode group 18 is formed by winding the positive electrode 15 and the negative electrode 16 with the separator 17 interposed therebetween.
[0097] Hereinafter, the present disclosure will be specifically described based on Examples and Comparative Examples, but the present disclosure is not limited to the following Examples.
[0098] <Examples 1 to 4>
[0099] The [Ni 0.90 Co 0.05 Al 0.05 The composite hydroxide represented by ](OH)2 was calcined at 500°C for 8 hours to obtain a metal oxide (Ni 0.90 Co 0.05 Al 0.05Next, LiOH and the above metal oxides were mixed so that the molar ratio of Li to the total amount of Ni, Co and Al was 1.03:1 to obtain a mixture. The mixture was placed under an oxygen flow with an oxygen concentration of 95% (per 10 cm 3 The mixture was calcined at a rate of 2 mL / min and a flow rate of 5 L / min per kg of the mixture), and then calcined from room temperature to 650°C at a temperature increase rate of 2.0°C / min, and then calcined from 650°C to 780°C at a temperature increase rate of 0.5°C / min to obtain a lithium-containing composite oxide (synthesis process).
[0100] Water was added to the lithium-containing composite oxide whose average particle size (D50) was adjusted to 10 μm so as to obtain a slurry concentration of 1500 g / L, and the mixture was stirred for 15 minutes and filtered to obtain a cake-like composition (washing step).
[0101] Particulate lithium methanesulfonate having an average particle size of 30 μm was added to the filter cake-like composition (addition step). The amount of lithium methanesulfonate added was 0.5% by mass relative to the mass of the lithium-containing composite oxide. After the addition step, a drying step was performed under vacuum at 180° C. for 2 hours to obtain the positive electrode active material of Example 1.
[0102] It should be noted that the presence of lithium sulfonate on the surface of the positive electrode active material was confirmed by Fourier transform infrared spectroscopy (FT-IR).
[0103] [positive electrode]
[0104] The positive electrode slurry is prepared by mixing 98 parts by mass of a positive electrode active material having lithium methanesulfonate on the surface, 1 part by mass of acetylene black as a conductive material, and 1 part by mass of polyvinylidene fluoride as a binding material, and mixing N-methyl-2-pyrrolidone (NMP) as a dispersion medium. The positive electrode slurry is applied to both sides of a positive electrode collector composed of thick aluminum foil, and after the coating is dried, the coating is rolled using a calendering roller and cut into a specified electrode size to obtain a positive electrode with a positive electrode mixture layer on both sides. An exposed portion exposed on the surface of the positive electrode collector is provided on a part of the positive electrode.
[0105] [negative electrode]
[0106] As the negative electrode active material, a mixture of silicon-containing material and artificial graphite in a mass ratio of 10:90 is used. 100 parts by mass of the negative electrode active material, 1 part by mass of sodium carboxymethyl cellulose (CMC-Na), and 1 part by mass of styrene-butadiene rubber (SBR) are mixed, and water is mixed as a dispersion medium to prepare a negative electrode slurry. The negative electrode mixture slurry is applied to both sides of a negative electrode collector composed of copper foil, and after the coating film is dried, the coating film is rolled using a calendering roller and cut into a specified electrode size to obtain a negative electrode having a negative electrode mixture layer on both sides. An exposed portion where the surface of the negative electrode collector is exposed is provided on a part of the negative electrode.
[0107] [Preparation of non-aqueous electrolyte]
[0108] Ethylene carbonate (EC), ethyl methyl carbonate (EMC), and dimethyl carbonate (DMC) were mixed in a volume ratio of 3:3:4. A non-aqueous electrolyte was prepared by dissolving lithium hexafluorophosphate (LiPF6) in the mixed solvent to a concentration of 1.2 mol / L. Any of the following sulfur-containing compounds was dissolved in the non-aqueous electrolyte at a content of 0.5 mass %.
[0109] (Lithium Fluorosulfate (LFS))
[0110]
[0111] (Methyl fluorosulfonate (MFS))
[0112]
[0113] (Propylene sultone (PRES))
[0114]
[0115] (Propane sultone (PS))
[0116]
[0117] [Preparation of test battery]
[0118] The positive electrode lead was attached to the exposed portion of the positive electrode, the negative electrode lead was attached to the negative electrode, and the positive electrode and the negative electrode were wound into a spiral shape with a polyolefin separator interposed therebetween, and then radially pressed to form a flat wound electrode group. The electrode group was housed in an outer casing composed of an aluminum laminate sheet, the above-mentioned nonaqueous electrolyte was injected, and then the opening of the outer casing was sealed to obtain test batteries (batteries A1 to A4).
[0119] [evaluate]
[0120] Under 45°C environment, constant current charging is performed at a specified current until the voltage of the non-aqueous electrolyte secondary battery reaches 4.2V, and then constant voltage charging is performed at a voltage of 4.2V. Next, constant current discharge is performed at a specified current until the voltage of the non-aqueous electrolyte secondary battery reaches 2.85V. The pause time between charging and discharging is set to 20 minutes. This cycle is repeated 300 times, and the discharge capacity of the 300th cycle is obtained.
[0121] The discharge capacities of batteries A1 to A4 when the discharge capacity of battery B2 of Comparative Example 2 described later is set as 100% are shown in Table 1. The larger the numerical value in Table 1, the better the charge-discharge cycle characteristics.
[0122] [Table 1]
[0123]
[0124] <Comparative Example 1>
[0125] Battery B1 of Comparative Example 1 was prepared in the same manner as in Example 1, except that lithium methanesulfonate was not added to the positive electrode active material and lithium fluorosulfonate was not included in the nonaqueous electrolyte, and was evaluated in the same manner as in Example 1.
[0126] <Comparative Example 2>
[0127] Battery B2 of Comparative Example 2 was prepared in the same manner as in Example 1, except that lithium fluorosulfonate was not contained in the nonaqueous electrolyte, and the same evaluation was performed.
[0128] <Comparative Examples 3 to 6>
[0129] Batteries B3 to B6 of Comparative Examples 3 to 6 were prepared in the same manner as in Examples 1 to 4 except that lithium methanesulfonate was not added to the positive electrode active material, and the same evaluation was performed.
[0130] As can be seen from Table 1, when lithium methanesulfonate is not added to the positive electrode active material, the sulfur-containing compound contained in the non-aqueous electrolyte has no effect of improving the capacity retention rate.
[0131] On the other hand, when lithium methanesulfonate is added to the positive electrode active material, the sulfur-containing compound contained in the non-aqueous electrolyte has a significant effect of improving the capacity retention rate.
[0132] [Additional Notes]
[0133] The present disclosure includes the following additional embodiments.
[0134] (1) A non-aqueous electrolyte secondary battery comprising a positive electrode, a negative electrode, and a non-aqueous electrolyte,
[0135] The positive electrode comprises a positive electrode active material,
[0136] The positive electrode active material includes a lithium-containing composite oxide and a sulfonic acid compound present on the surface of the lithium-containing composite oxide.
[0137] The nonaqueous electrolyte includes a sulfur-containing compound.
[0138] (2) The nonaqueous electrolyte secondary battery according to (1) above, wherein the sulfonic acid compound is represented by the general formula (I):
[0139]
[0140] In the general formula (1), A is a Group 1 element or a Group 2 element, R is a hydrocarbon group, and n is 1 or 2.
[0141] (3) The nonaqueous electrolyte secondary battery according to (1) or (2) above, wherein A is a Group 1 element.
[0142] (4) The nonaqueous electrolyte secondary battery according to any one of (1) to (3) above, wherein A is Li.
[0143] (5) The nonaqueous electrolyte secondary battery according to any one of (1) to (4) above, wherein R is an alkyl group.
[0144] (6) The nonaqueous electrolyte secondary battery according to any one of (1) to (5) above, wherein R is a methyl group.
[0145] (7) The nonaqueous electrolyte secondary battery according to any one of (1) to (6) above, wherein the amount of the sulfonic acid compound present on the surface of the lithium-containing composite oxide is 0.1 mass % or more and 1 mass % or less relative to the mass of the lithium-containing composite oxide.
[0146] (8) The nonaqueous electrolyte secondary battery according to any one of (1) to (7) above, wherein the content of the sulfur-containing compound in the nonaqueous electrolyte is 0.01 mass % or more and 10 mass % or less.
[0147] (9) The nonaqueous electrolyte secondary battery according to any one of (1) to (8) above, wherein the sulfur-containing compound has one or more sulfonyl groups.
[0148] (10) The nonaqueous electrolyte secondary battery according to any one of (1) to (9) above, wherein the sulfur-containing compound has one or more fluorosulfonyl groups.
[0149] (11) The nonaqueous electrolyte secondary battery according to any one of (1) to (10) above, wherein the sulfur-containing compound includes lithium fluorosulfonate.
[0150] (12) The nonaqueous electrolyte secondary battery according to any one of (1) to (11) above, wherein the sulfur-containing compound includes a cyclic sulfonic acid ester.
[0151] (13) A non-aqueous electrolyte secondary battery according to any one of (1) to (12) above, wherein the proportion of Ni in the metal elements other than Li contained in the lithium-containing composite oxide is greater than 50 atomic %, the proportion of Co is greater than 0 atomic % and less than 20 atomic %, the proportion of Al is greater than 0 atomic % and less than 10 atomic %, and the proportion of Mn is greater than 0 atomic % and less than 50 atomic %.
[0152] (14) The nonaqueous electrolyte secondary battery according to any one of (1) to (13) above, wherein the negative electrode contains a negative electrode active material.
[0153] The negative electrode active material includes a carbon material and a silicon-containing material.
[0154] Industrial Applicability
[0155] The nonaqueous electrolyte secondary battery according to the present disclosure can be used as a main power source for mobile communication devices, electric vehicles, hybrid vehicles, portable electronic devices, and the like.
[0156] The preferred embodiments of the present invention are described, but the disclosure thereof shall not be interpreted as restrictive. It is obvious to those skilled in the art that various modifications and changes can be clearly understood by reading the above disclosure. Therefore, the attached claims should be interpreted as including all modifications and changes that do not depart from the true spirit and scope of the present invention.
[0157] Description of Reference Numerals
[0158] 10: non-aqueous electrolyte secondary battery, 11: sealing body, 12: valve body, 13: metal plate, 14: insulating member, 15: positive electrode, 15a: positive electrode lead, 16: negative electrode, 16a: negative electrode lead, 17: separator, 18: electrode group, 21: sealing gasket, 22: battery can, 22a: annular groove, 23: first insulating plate, 24: second insulating plate
Claims
1. A non-aqueous electrolyte secondary battery comprising a positive electrode, a negative electrode and a non-aqueous electrolyte, The positive electrode comprises a positive electrode active material, The positive electrode active material includes a lithium-containing composite oxide and a sulfonic acid compound present on the surface of the lithium-containing composite oxide. The nonaqueous electrolyte includes a sulfur-containing compound.
2. The nonaqueous electrolyte secondary battery according to claim 1, wherein The sulfonic acid compound is represented by the general formula (I), In the general formula (I), A is a Group 1 element or a Group 2 element, R is a hydrocarbon group, and n is 1 or 2.
3. The nonaqueous electrolyte secondary battery according to claim 1, wherein The A is a Group 1 element.
4. The nonaqueous electrolyte secondary battery according to claim 1, wherein The A is Li.
5. The nonaqueous electrolyte secondary battery according to claim 1, wherein The R is an alkyl group.
6. The nonaqueous electrolyte secondary battery according to claim 1, wherein The R is a methyl group.
7. The nonaqueous electrolyte secondary battery according to any one of claims 1 to 5, wherein The amount of the sulfonic acid compound present on the surface of the lithium-containing composite oxide is 0.1 mass % or more and 1 mass % or less relative to the mass of the lithium-containing composite oxide.
8. The nonaqueous electrolyte secondary battery according to any one of claims 1 to 5, wherein The content of the sulfur-containing compound contained in the nonaqueous electrolyte is 0.01 mass % or more and 10 mass % or less.
9. The nonaqueous electrolyte secondary battery according to any one of claims 1 to 5, wherein The sulfur-containing compound has one or more sulfonyl groups.
10. The nonaqueous electrolyte secondary battery according to any one of claims 1 to 5, wherein The sulfur-containing compound has one or more fluorosulfonyl groups.
11. The nonaqueous electrolyte secondary battery according to claim 10, wherein The sulfur-containing compound comprises lithium fluorosulfonate.
12. The nonaqueous electrolyte secondary battery according to any one of claims 1 to 5, wherein The sulfur-containing compound comprises a cyclic sulfonate ester.
13. The nonaqueous electrolyte secondary battery according to any one of claims 1 to 5, wherein Among the metal elements other than Li contained in the lithium-containing composite oxide, the proportion of Ni is 50 atomic % or more, the proportion of Co is 0 atomic % or more and 20 atomic % or less, the proportion of Al is 0 atomic % or more and 10 atomic % or less, and the proportion of Mn is 0 atomic % or more and 50 atomic % or less.
14. The nonaqueous electrolyte secondary battery according to any one of claims 1 to 5, wherein The negative electrode comprises a negative electrode active material, The negative electrode active material includes a carbon material and a silicon-containing material.
Citation Information
Patent Citations
Lithium titanate powder for power storage device electrode, active substance material, and power storage device using the active substance material
JP2018006164A